Volunteers’ intention of community garden program in the Klang Valley, Malaysia - Ramalingam, Leelanayagi (2018)
Community Garden Program is one of the Urban Agricultural Program in Malaysia which is supported by governmental policies and organization efforts as it is viewed as the most effective remedy to future challenges such as population growth, food security and increase in food price. Community Garden Program is depends on volunteers’ help as they are responsible to carry out the daily gardening activities. Thus, the sustainability of the program is highly associated with committed volunteers. However, attracting and retaining volunteers for the program had become the major challenges. Consequently, all of the gardening activities were carried out by few volunteers. This lead to lack of interest among the volunteers and few community gardens were abandoned. Therefore, there is a need to understand factors that influence volunteers’ continued participation in the program. Nevertheless, no studies have been done on community garden volunteers’ intention to remain. Therefore, this study aims to fill the gap by understanding what drive the volunteers’ retention in order to sustain the Community Garden Program in the future. The general objective of the study is to measure the volunteers’ intention to remain in the Community Garden Program. To achieve this, data was collected from 390 volunteers of the Community Garden Program around Klang Valley, Malaysia. The seven (7) sections of the questionnaire are socio demographic characteristics, social support, community and country involvement, self-image congruency, motivation, satisfaction and intention to remain as volunteers. The result of the Partial Least Square Structural Equation Modeling revealed that social support, community and country involvement and self-image congruency influence motivation. Moreover, self-image congruency and motivation were significant predictors of satisfaction. Also, community and country involvement, motivation and satisfaction have positive effect on intention to remain as volunteers in the Community Garden Program. The mediation effect analysis of satisfaction showed positive result. The result of the binary logistic regression found that male respondents who aged 49 years old and above with high-income level are more likely to remain as volunteers in the Community Garden Program. As a conclusion, community and country involvement, motivation, satisfaction, age, gender and income level were the significant predictors of intention to remain as volunteers in the Community Garden Program. Hence, the government organizations need to ensure that the volunteers are motivated by the governmental support to be involved in the program and satisfied with their volunteer tasks for their continuous involvement in the program. Besides, it is important to promote the Community Garden Program among male urban dwellers who aged 49 years old and above with high income as this group of people are more likely to remain as volunteers in the program. These are essential for the sustainability of the Community Garden Program.